Creep of geopolymeric concrete obtained from mining tailings - Huamán-Mamani F.A. (2020)
Geopolymeric materials have recently been considered a revolutionary class of materials, due to the diversity of applications where they can be used, this derived from their good mechanical resistance, thermochemical stability and good fire resistance. From 1970 to the present, a notable increase has been observed in the number of scientific publications dealing with the synthesis and applications of geopolymeric materials with industrial application. Several publications have reported geopolymers as alternative materials to Portland cement, which will allow having a green construction industry in the coming years. The elaboration of geopolymeric materials is relatively simple, beginning with the identification of a source rich in amorphous aluminosilicates and a hardening compound (mainly alkaline in nature) which are properly mixed until a homogeneous and workable paste is obtained, then can harden at room temperature and acquire good mechanical resistance in a few hours. On the other hand, mining in Peru is one of the most important industries due to its contribution to the economic development of the country. However, mining is also one of the industries with the greatest negative impact on the environment, mainly due to the enormous amount of inorganic waste that it generates and which is currently accumulated without any prospect of recycling or reuse. Therefore, this research was conducted to elaborate concretes from mining tailings and to evaluate their mechanical behavior in creep (between 500 and 600 ºC). The results obtained allow us to propose the use of mining tailings for the elaboration of geopolymeric thermal barriers that work in conditions of intermediate temperatures, up to 600 ºC. © 2020, Avestia Publishing. All rights reserved.